Nhiễm khuẩn vết mổ do vi khuẩn đa kháng tại Bệnh viện Trung ương Huế - Phồn, Đặng Như; Luyện, Trần Hữu; Liên, Nguyễn Thị Nam; Hằng, Phạm Vũ Thúy; Trâm, Nguyễn Đình Ngọc; Phượng, Trần Thị Thúy (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.